(untitled) (Samsad Journal संसद जर्नल, 2024)
This research paper explores the potential implications of implementing the Hybrid Annuity Model (HAM) in the development of highways in Nepal. Drawing upon existing literature, case studies from other countries, the paper evaluates the suitability of HAM within the context of Nepal’s infrastructure needs and socio-economic conditions. It also offers policy recommendations for the adoption and implementation of HAM in Nepalese highway projects.